Eksistensi Pondok Pesantren Irsyadul Islamiyah Dalam Mewujudkan Nilai Toleransi di Desa Tanjung Medan - Syahputra Nasution, Kurnia; Indra, Indra (Jayapangus Press, 2025)
The background of this study departs from the importance of pesantren as a traditional Islamic educational institution that contributes to shaping the character of a moderate and inclusive society. Thus, this study discusses the role of the Irsyadul Islamiyah Islamic Boarding School in realizing the value of tolerance in Tanjung Medan Village. The purpose of this study is to analyze how pesantren play a role in instilling the values of religious tolerance and moderation in a plural society. This study uses a qualitative method with a descriptive-analytical approach, where data is collected through interviews with teachers in the pesantren environment. The results of the study show that the Irsyadul Islamiyah Islamic Boarding School contributes significantly to building tolerance through the implementation of a moderation-based curriculum, the example of the kiai and ustadz, as well as active participation in social activities and interfaith dialogue. Supporting factors include community involvement and contextual curriculum adaptation, while the challenges faced are rigid religious understanding and lack of interaction with non-Muslim communities. In conclusion, the Irsyadul Islamiyah Islamic Boarding School has great potential in strengthening social harmony and instilling the values of tolerance through a moderate and inclusive educational approach.